Popular politics and political culture in Upper Canada, 1800-1850 - Wilton, Carol (McGill-Queen's University Press, 2000)
"In Popular Politics and Political Culture in Upper Canada, 1800-1850 Carol Wilton shows that ordinary Canadians were much more involved in the political process that previously believed. Wilton demonstrates how the dissidents in Upper Canada challenged established patterns of paternalism, subverted official notions of hierarchy, and promoted the development of an expanded public sphere in ways that had a lasting influence on the province's political culture." "She reveals that petitioning movements, which were connected not only with public meetings but with demonstrations and parades, were also associated with political violence. Wilton argues that the resulting assaults, riots, and effigy-burnings - all prominent features of Tory governance - not only contributed to the striking political polarization of the population but also helped provoke the Rebellion of 1873"--Jacket